Akad Syirkah (Kemitraan) dan Mudharabah (Bagi Hasil) serta Pengaplikasiannya dalam Pembiayaan Usaha Produktif - Husna, Zahra Maulidatul; Afida, Ila Nur; Rohmah, Nabilla Ni`matur; Fadhila, Fadhila; Azahra, Intan Muthia; Ramadhani, Allya Lubna Octavia; Kurniawan, Taufiq (Jurnal ini dipublikasikan oleh Pusat Penelitian dan Pengabdian Publikasi (P3M) STAI Nahdlatul Watan Samawa-licensed under a Creative Commons Attribution-ShareAlike 4.0 International License., 2025)
Syirkah and mudharabah are two forms of partnership contracts widely applied in financing productive business activities within Islamic financial institutions. Both contracts are based on the principles of profit and loss sharing and the prohibition of riba, which promote fairness and ethical economic practices. However, their implementation in society still faces challenges due to limited understanding of their conceptual distinctions, mechanisms, and risk-sharing characteristics. This article describes the concepts of syirkah and mudharabah, including their essential elements and operational requirements, as well as their application in productive financing schemes. In syirkah, all partners contribute capital and/or managerial efforts and are entitled to profits according to the mutually agreed ratio, while losses are borne proportionally based on each partner’s contribution. In contrast, mudharabah involves a collaboration in which the investor provides capital and the entrepreneur manages the business. Profits are distributed based on a predetermined profit-sharing ratio, while financial loss is borne solely by the investor, as long as the entrepreneur is not negligent or in breach of trust. The analysis indicates that both contracts have significant potential to support the development of micro, small, and medium enterprises (MSMEs) and strengthen the Islamic economic system. Nevertheless, the selection of the appropriate contract must consider the business characteristics, the capabilities of the parties involved, and the level of risk they are willing to bear. With accurate understanding and implementation, syirkah and mudharabah can serve as transparent, equitable, and sharia-compliant financing solutions for the community.